Antimicrobial Activity Test of Ethanol Extract of Senggani Leaves (Melastoma malabraticum L) Against Propionibacterium Acnes and Staphylococcus Epidermidis - Nasution, Haris Munandar; Rani, Zulmai; Fauzi, Ziza Putri Aisyia; Ridho, Ahmad Rasyid (Jurnal Sains dan Kesehatan, 2024)
Senggani leaves are a plant that can be found in Indonesia, including hilly locations. The people of Marendal, Patumbak subdistrict, believe that senggani leaves may heal minor skin wounds. The goal of this study was to identify the class of secondary metabolite chemical compounds and their antibacterial efficacy against the microorganisms Propionibacterium acnes and Staphylococcus epidermidis at 5, 10, and 20% concentrations. The ethanol extract of senggani leaves contains secondary metabolite compounds with antibacterial activity. According to the antibacterial test results, a 20% ethanol extract of senggani leaves is effective against Propionibacterium with a diameter of 10.7 mm, a 10% in the medium category with a diameter of 9.27 mm, and a 5% in the medium category with a diameter of 8.8 mm. Meanwhile, the diameter of Staphylococcus epidermidis at a 20% was 8.77 mm in the medium category, 8.37 mm at 10%, and 8.6 mm at a 5% concentration.   Keywords:          Propionibacterium acnes, Senggani leaves, Staphylococcus epidermidis